Upper esophageal sphincter augmentation reduces pharyngeal reflux in nasogastric tube–fed patients. (8th October 2017) - Jiao, Hongmei; Mei, Ling; Liang, Chenyang; Dai, Yun; Fu, Zhifang; Wu, Lihong; Sanvanson, Patrick; Shaker, Reza
Abstract : Objectives/Hypothesis: Aspiration of gastric refluxate is one of the most commonly observed complications among long‐term nasogastric tube (NGT) fed patients. The upper esophageal sphincter (UES) pressure barrier is the main defense mechanism against pharyngeal reflux of gastric contents. Our objective was to investigate the efficacy and safety of the UES assist device (UES‐AD) in preventing gastric reflux through the UES in long‐term NGT‐fed patients. Study Design: Self‐Controlled Case series. Methods: We studied 10 patients (mean age = 90.6 ± 3.4 years, four females) with dysphagia caused by stroke or dementia who were fed for 0.5 to 5 years (median = 3 years) by NGT. External pressures of 20 to 30 mm Hg were applied by using a handmade UES‐AD, which was started 2 hours after the beginning of NGT infusion and was alternated between periods of 2 hours on and 2 hours off, for a total of 12 hours. Placement of the impedance sensors within the UES was guided by high‐resolution manometry. Trans‐UES and intraesophageal reflux events were recorded by using 24‐hour combined pH‐impedance measurements. Results: No aspiration pneumonia events were noted in the period 1 month before or during the study in any of the cohort. Baseline UES pressure averaged 17.5 ± 9.4 mm Hg and was increased to 38.9 ± 11.9mm Hg after application of the UES‐AD. Overall frequency of trans‐UES reflux decreased significantly with the UES‐AD compared to without (0.8 ± 0.9 vs. 3.3 ± 2.8, P < .05 for the 12‐hour study period). There was no effect of the UES‐AD on esophageal reflux events (7.4 ± 4.4 vs. 6.4 ± 3.0, P > .05). Conclusions: UES‐AD significantly decreases the number of trans‐UES reflux events and can potentially reduce the aspiration risk associated with NGT feeding. Level of Evidence: 4. Laryngoscope, 128:1310–1315, 2018